Hydration: Special issues for playing football in warm and hot environments - Shirreffs, S. M. (Scandinavian Journal of Medicine & Science in Sports, 2010)
The high metabolic rates and body temperatures sustained by football players during training and matches causes sweating - particularly when in warm or hot environments. There is limited published data on the effects of this sweat loss on football performance. The limited information available, together with knowledge of the effects of sweat loss in other sports with skill components as well as endurance and sprint components, suggests that the effects of sweating will be similar as in these other activities. Therefore, the generalization that, on average, a body mass reduction equivalent to 2% should be the acceptable limit of sweat losses seems reasonable. This magnitude and more, of sweat loss is a common occurrence for some players. Sodium is the main electrolyte lost in sweat but there is large variability in sodium losses between players. However, the extent of sodium losses in some players may be such that its replacement is warranted for these players. Although football is a team sport, the great individual variability in sweat and electrolyte losses of players in the same training session or match dictates that individual monitoring to determine individual water and electrolyte requirements should be an essential part of a player's nutrition strategy.